Effect of Antibiotic Therapy on the Outcome of Frozen-thawed Embryo Retransfer Following Failed First Implantation in Women with Chronic Endometritis - Longlong WEI, Cuilian ZHANG (Zhongguo quanke yixue, 2022)
Background Chronic endometritis (CE) refers to chronic inflammatory condition of the endometrium. Recent studies have found that CE is closely associated with infertility, recurrent miscarriage, and recurrent implantation failure. However, there are no studies on CE prevalence in patients with first implantation failure and the outcome of re-pregnancy by assisted reproductive technology in these patients after antibiotic treatment. Objective To investigate CE prevalence in women who used in vitro fertilization & embryo transfer (IVF-ET) to assist in achieving a pregnancy but had failed first implantation and the impact of antibiotic treatment on the outcome of the next frozen-thawed embryo transfer in this group. Methods Women (n=381) who received IVF-ET to assist in achieving a pregnancy but had failed first implantation were selected from Henan Provincial People's Hospital from May 2017 to May 2021. 333 patients without CE were according to hysteroscopic and endometrial histopathological findings. 37 of CE patients were found with reversed (cured) clinical condition, but the other 11 still with unreversed (uncured) condition who were received antibiotic treatment . Clinical data and the outcome of the second assisted conception were compared between cured and uncured CE patients, as well as non-CE patients. Results Cured and uncured CE patients and non-CE patients had no statistical differences in mean age, BMI, endometrial thickness on the day of embryo transfer, years of infertility, and number of embryos transferred, as well as the distribution of infertility type (P>0.05) . But they had statistical differences in success rates of embryo retransfer and pregnancy (P<0.05) . Cured CE patients and non-CE patients had higher success rates of embryo retransfer and pregnancy than did uncured CE patients (P<0.05) . There were no statistical differences in early abortion rates were found across cured and uncured CE patients and non-CE patients (P>0.05) . Conclusion CE should be treated by standard antibiotic treatment. Uncured CE may negatively influence the outcome of frozen-thawed embryo retransfer. So it is recommended that women with first implantation failure actively undergo hysteroscopy and endometrial histopathology so as to find possible causes of implantation failure.